Importance measure method for error sources of degradation systems based on the present worth of expected Taguchi quality loss. (29th January 2020) - Sun, Zhongchao; Yu, Tianxiang; Cui, Weimin; Song, Bifeng
Abstract: Deteriorating of the error sources and the deviation of the quality characteristic (QC) of the product from the target value are ubiquitous in practice. Studying the relative contribution of the error sources to the QC deviation is helpful for improving the product performance effectively. In this study, we propose an error importance measure (EIM) method to quantify the relative contribution of error sources to the Taguchi quality loss that is caused by the QC deviation. The present worth of the expected Taguchi quality loss (ETQL) is used to characterize the deteriorating QC deviation. We use Taylor series expansion to decompose the time‐dependent ETQL and the present worth of ETQL into a series of fractions, representing the individual and the interaction contributions of the error sources. Based on the decomposition, the time‐dependent and the time‐independent EIM indices for one and a group of error sources are defined, respectively. The evaluation procedure for the EIM indices is provided and the properties are discussed. Finally, we provide a realistic application case to an aircraft wheel door mechanism to demonstrate the effectiveness of the proposed EIM method.